Relation between Renal Function and Insulin Resistance of Type 2 Diabetic Iraqi Patients - Rami Fadhel Lefta; Ekhlas Abdallah Hassan (Academic Science Journal)
Type 2 diabetes mellitus (T2DM) is a condition where the body's ability to regulate and utilize glucose as fuel is compromised. As a result of this chronic ailment, excess sugar circulates in the bloodstream. Thus, it can be described as a cluster of metabolic disorders that manifest through factors like insulin resistance and give rise to various complications. These conditions impact several physiological organs, leading to reduced efficiency in their functioning. The objective of this study was to assess the level of insulin in patients with Type 2 diabetes mellitus (T2DM) and to interpret the relationship between insulin resistance (HOMA-IR) and renal function. The methods employed in this investigation were designed to achieve these specific aims, seventy patients and twenty controls were involved for this study. The patients of T2DM was divided into three group according to them eGFR, 20 stage I patients (G1), 25 stage II diabetic patients (G2) and 25 stage III diabetic patients (G3). Insulin, fasting plasma glucose (FBG), HbA1c, and renal function were measured in all subject. The study's findings indicated that patients in Group 3 (G3) with elevated glomerular filtration rate (GFR) exhibited significantly higher insulin levels (14.48 μIU/ml) and HOMA-IR values (8.66) compared to other patients. Moreover, diabetic patients had significantly higher serum insulin levels than those in the healthy control group (P<0.001). The diabetic group also demonstrated a marked